Humans : perspectives on our evolution from world experts - Almecija, Sergio (New York : Columbia University Press, 2023)
"When Sergio Almécija was a new assistant professor tasked with teaching human evolution, he found it nearly impossible to summarize the myriad scientific points of view. He began to wonder what other researchers felt were the most relevant aspects of their own research and what they thought was the meaning and impact of the work they did. So, he compiled a list of the top experts across paleontology, primatology, human genetics, behavior, and other disciplines and asked them to respond to a handful of questions: Which discovery would you highlight as a game-changer in the way we look at human evolution, and how did it influence your own career? What can human evolutionary studies teach us about our past that can be helpful for our present or future? Are humans "special"? And a few others. He received responses from an impressive group, including Richard Leakey, Richard Wrangham, Nina Jablonski, CUP author Ian Tattersall, Robert Sapolsky, Leslea Hlusko, and many more, totaling just over 100 contributions in all. The book is a compilation of the experts' answers to these questions, lightly edited. The overall goal is to offer a personable, interesting, cross-disciplinary, and thought-provoking source of different (often opposite) ideas around our past and future-key aspects usually inspected separately."--
Includes index.
Keywords: Human beings -- Origin; Human evolution